PERSONALLY ORIENTED LEARNING AS FACTOR OF STIMULATION OF CREATIVE STUDENT ACTIVITIES (Pedagogy of Higher and Secondary Education, 2022)
The article grounds the necessity of modernization of preparation of specialists on condition o f higher school. The assent is made on personally oriented teaching as the factor of stimulating creative activity o f students, their readiness to creative professional activities.